[tex] \frac{x}{0.(6)} = \frac{0.(3)}{ \frac{3}{8} } \\ [/tex]
[tex]x = \frac{0.(6) \times 0.(3)}{ \frac{3}{8} } = \frac{ \frac{6}{9} \times \frac{3}{9} }{ \frac{3}{8} } = \frac{6}{9} \times \frac{3}{9} \times \frac{8}{3} = \frac{16}{27} \\ [/tex]
Ответ:
Пошаговое объяснение:
0,(6) = (6-0)/9 = 6/9 = 2/3
0,(3) = (3-0)/9 = 3/9 = 1/3
х : 0,(6) = 0,(3)
х : 2/3 = 1/3
х = 1/3 * 2/3
х = 2/9
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex] \frac{x}{0.(6)} = \frac{0.(3)}{ \frac{3}{8} } \\ [/tex]
[tex]x = \frac{0.(6) \times 0.(3)}{ \frac{3}{8} } = \frac{ \frac{6}{9} \times \frac{3}{9} }{ \frac{3}{8} } = \frac{6}{9} \times \frac{3}{9} \times \frac{8}{3} = \frac{16}{27} \\ [/tex]
Ответ:
Пошаговое объяснение:
0,(6) = (6-0)/9 = 6/9 = 2/3
0,(3) = (3-0)/9 = 3/9 = 1/3
х : 0,(6) = 0,(3)
х : 2/3 = 1/3
х = 1/3 * 2/3
х = 2/9